Dichlorido[(4E,11E)-5,7,12,14-tetrabenzyl-7,14-dimethyl-1,4,8,11-tetra azacyclotetradeca-4,11-diene]cobalt(III) perchlorate - Roy, T.G.; Hazari, S.K.S.; Barua, K.K.; Ng, S.W.; Tiekink, E.R.T. (International Union of Crystallography, 2011)
The Co(III) atom in the title complex, [CoCl(2)(C(40)H(48)N(4))]ClO(4), is octahedrally coordinated within a trans-Cl(2)N(4) donor set provided by the tetradentate macrocylic ligand and two chloride ions. The N-H atoms, which are orientated to one side of the N(4) plane, form hydrogen bonds with chloride ions and perchlorate-O atoms. These along with C-H center dot center dot center dot O interactions consolidate the three-dimensional crystal structure. One of the benzene rings was disordered. This was resolved over two positions with the major component of the disorder having a site-occupancy factor of 0.672 (4).